Metafizyczne enklawy w prozie Stefana Żeromskiego - Kielak, Dorota (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The articles presents an interpretation of selected topics from the Stefan Żeromski’s novel which form an articulation of the nineteenth century changes taking place within the metaphysics. The scene in which the protagonists from Żeromski’s novels experienced communication with the dead and lived through the inner enlightenment have been analyzed. The article also describes the poetics of articulation of metaphysical experience in the prose of Żeromski paying particular attention to the theme of light equivalentizing the internal initiation of heroes, leading them mainly to cross the barriers of death. From this perspective, the articles interprets such motives as birch, earth and kiss as functionalizing metaphysical experience of the heroes described in the novels. The analysis of these metaphysical enclaves in the prose of Żeromski allowed to put forward the thesis that the metaphysics of the writer is not inspired by philosophy or theology of the late nineteenth and early twentieth century, but by faith in the strength of family and native ties and by the power of human community which leads man into another dimension of reality.